Appreciation and illegitimate tasks as predictors of affective well-being : Disentangling within- and between-person effects - Pfister, Isabel B. (Colegio Oficial de Psicólogos de Madrid, 2020)
This study examines the effects of appreciation and illegitimate tasks on affective well-being. As empirical results often refer to inter-individual effects but are interpreted in terms of intra-individual effects, we try to disentangle the two. In longitudinal multilevel structural equation models with data of 308 participants, appreciation predicted affective well- being in the expected direction both on the within-level and the between-level, whereas illegitimate tasks had a stronger effect on the between level. On the within-level, appreciation buffered the effect of illegitimate tasks for two of the four facets of affective well-being. Demonstrating a convergent and pervasive effect of appreciation on both levels but diverging effects of illegitimate tasks implies that finding on one level may, but need not, work on the other level as well.